Ensaios sobre desempenho socioeconômico, complexidade econômica e performance ambiental - Simões, Marcelo Silva (2021)
This thesis is dedicated to the investigation of the relationships between economy and environment through the debate of socioeconomic development, economic complexity and environmental performance. A transdisciplinary perspective is sought, involving contributions from schools of systems theory, institutionalist, evolutionary, economic-ecological and post-Keynesianism. The first essay is dedicated to the definition of the theoretical-analytical framework in which the complexities of the real relations between economy and the environment are understood. The effort to concatenate the theoretical contributions that facilitate the analysis of the reality of these relationships is fundamental to be able to format a holistic view capable of interpreting the empirical results and the proposals for public policies that follow. The second essay aims to empirically assess the role of economic complexity as an improvement in environmental performance. Additionally, it discusses the concept of decoupling in its impact and resource dimensions. We start from the hypothesis that economic complexity has different impacts in terms of speed of occurrence when these two dimensions of the concept are taken into account. The empirical test involved annual data for a set of 115 countries for the period 1995-2015, making up the structure of a short data panel. We opted for the strategy of subdividing the database into two parts: more complex countries and less complex countries. In general, for the more complex countries, the trend towards decoupling resources and impact occurs more uniformly and more robustly in the decarbonization of the economy. On the other hand, the behavior for less complex countries was the opposite: greater ease in decoupling resources and greater intensification of impact variables. The third essay was responsible for diagnosing the inadequacy of decoupling as an effective instrument for achieving the transition to a low-carbon economy suited to ecosystem limits, in particular, in relation to the goals of the Paris Agreement. A proposal for a development strategy was structured that is compatible with the search for sufficiency of basic human needs and dignity of freedom of choice, in a more realistic scenario of the need to reduce the final demand for energy use in order to limit the global warming at 1.5ºC by 2100, from macroeconomic policies within the post-Keynesian framework that encompass the notion of environmental sustainability, and microeconomic policies - in particular, "green industrial" - that enable the performance of the State and the initiative in a “green complexification strategy”. Thus, developing countries, less complex, would have a “shortcut” to achieve socioeconomic prosperity, with less intensity of environmental degradation and respect for ecosystem limits.